Hospital Accountability for Medical Malpractice within Civil Liability and Patient Safety Governance - Arfandi Sanubari (Punggawa Legacy Center, 2026)
Hospital liability in medical malpractice has become an important issue because modern care is delivered through institutional systems that shape clinical decisions, patient safety, and legal responsibility. This study aims to examine the scope of hospital accountability when patient injury results from negligent medical services, unsafe governance, inadequate supervision, or breach of patient rights. The research applies a normative juridical method with descriptive analysis of legal doctrine, health law principles, civil liability, administrative responsibility, criminal responsibility, and patient safety scholarship. The findings show that hospitals may be liable through vicarious responsibility for negligent health workers, direct institutional negligence, civil compensation duties, regulatory sanctions, and limited criminal accountability in serious cases. Hospital responsibility is strengthened by failures in credentialing, staffing, informed consent, documentation, incident reporting, disclosure, and digital health governance. Effective liability should distinguish unavoidable medical risk from malpractice while ensuring patient compensation, institutional correction, and safer health service systems.